Genetics of complex disease - Donaldson, Peter; Daly, Ann K.; Ermini, Luca; Bevitt, Debra (Garland Science, 2016)
Genetics of Complex Disease examines how the identification of genetic variations that increase or reduce the risk of common, genetically complex, diseases can be used to improve our understanding of the pathology of many common diseases; enable better patient management and care; and help with differential diagnosis. It starts with the quest